ATG7-mediated autophagy facilitates embryonic stem cell exit from naive pluripotency and marks commitment to differentiation. Issue 12 (2nd December 2022) - Zhou, Jilong; He, Hainan; Zhang, Jing-Jing; Liu, Xin; Yao, Wang; Li, Chengyu; Xu, Tian; Yin, Shu-Yuan; Wu, Dan-Ya; Dou, Cheng-Li; Li, Qiao; Xiang, Jiani; et al.
ABSTRACT: Macroautophagy/autophagy is a conserved cellular mechanism to degrade unneeded cytoplasmic proteins and organelles to recycle their components, and it is critical for embryonic stem cell (ESC) self-renewal and somatic cell reprogramming. Whereas autophagy is essential for early development of embryos, no information exists regarding its functions during the transition from naive-to-primed pluripotency. Here, by using an in vitro transition model of ESCs to epiblast-like cells (EpiLCs), we find that dynamic changes in ATG7-dependent autophagy are critical for the naive-to-primed transition, and are also necessary for germline specification. RNA-seq and ATAC-seq profiling reveal that NANOG acts as a barrier to prevent pluripotency transition, and autophagy-dependent NANOG degradation is important for dismantling the naive pluripotency expression program through decommissioning of naive-associated active enhancers. Mechanistically, we found that autophagy receptor protein SQSTM1/p62 translocated into the nucleus during the pluripotency transition period and is preferentially associated with K63 ubiquitinated NANOG for selective protein degradation. In vivo, loss of autophagy by ATG7 depletion disrupts peri-implantation development and causes increased chromatin association of NANOG, which affects neuronal differentiation by competitively binding to OTX2-specific neuroectodermal development-associated regions. Taken together, our findings reveal that autophagy-dependent degradation of NANOG plays a critical role in regulating exit from the naive state and marks distinct cell fate allocation during lineage specification. Abbreviations: 3-MA: 3-methyladenine; EpiLC: epiblast-like cell; ESC: embryonic stem cell; PGC: primordial germ cell